2014
DOI: 10.1111/mec.12661
|View full text |Cite
|
Sign up to set email alerts
|

Low interbasin connectivity in a facultatively diadromous fish: evidence from genetics and otolith chemistry

Abstract: Southern smelts (Retropinna spp.) in coastal rivers of Australia are facultatively diadromous, with populations potentially containing individuals with diadromous or wholly freshwater life histories. The presence of diadromous individuals is expected to reduce genetic structuring between river basins due to larval dispersal via the sea. We use otolith chemistry to distinguish between diadromous and nondiadromous life histories and population genetics to examine interbasin connectivity resulting from diadromy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 63 publications
7
44
1
Order By: Relevance
“…Miller et al, 2005;Schmidt et al, 2011aSchmidt et al, , 2014Hughes et al, 2014). By combining analyses of otolith chemistry and genetic markers, it is possible to gain powerful insights into the role of migration in structuring populations of fish over a range of temporal and spatial scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miller et al, 2005;Schmidt et al, 2011aSchmidt et al, , 2014Hughes et al, 2014). By combining analyses of otolith chemistry and genetic markers, it is possible to gain powerful insights into the role of migration in structuring populations of fish over a range of temporal and spatial scales.…”
Section: Discussionmentioning
confidence: 99%
“…Cook et al, 2011;Schmidt et al, 2011a;Page et al, 2012;Hughes, Huey & Schmidt, 2013;Hughes et al, 2014). Molecular markers are often used to explore the life history of diadromous species (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the typically strong regional phylogeographic structure detected within southern Australia's freshwater‐limited taxa (above), relatively shallow genetic structure has been detected in riverine taxa that can potentially tolerate estuarine and/or marine conditions (e.g. Philypnodon : Thacker, Unmack, Matsui, Duong, & Huang, ; Galaxias brevipinnis : Waters, Shirley, & Closs, ; Paratya : Cook et al, ; but note regional differentiation in Retropinna : Hammer, Adams, Unmack, & Walker, ; Hughes, Schmidt, MacDonald, Huey, & Crook, ).…”
Section: Southeast Australian Freshwater Phylogeogeographymentioning
confidence: 94%
“…A number of phylogeographic studies on amphidromous species have revealed a lack of geographic structure and high levels of gene flow over scales from hundreds to thousands of kilometres, e.g. neritid snails [14], [15], gobiid fish [16] as well as atyid and palaemonid shrimps [17], although there are exceptions [18]. …”
Section: Introductionmentioning
confidence: 99%